COMMON PEOPLE IN CARL SANDBURG’S POEMS AND WIJI THUKUL’S : A COMPARATIVE STUDY - Mrs JULIATI, M.Hum. (ISSN)
Both Carl Sandburg and Wiji Thukul are poets whose poems mostly deal with the lives and struggles of common people. Due to this similarity, comparative study is worth doing to dig out more deeply the similarities and the distinctions that may exist due to the different as well as similar social–historical experiences of the poets. The study results that both poets share a similar vision of common people. Both attempt to elevate the condition of common people. Yet the slightly different social-historical experiences enhance a small distinctive attitude. Sandburg tends to insert his admiration as well as pride of being common people in his poems while Wiji Thukul does not.